Comparison of thyroid hormones reference intervals based on thyroid antibody levels: A multicenter study - Havva Beyter; Osman Acar; Oytun Portakal; Özlem Gülbahar; Gülsüm F. Türkeş; Neslihan Yıldırım Saral; Muhittin Abdülkadir Serdar; Aysel Ozpinar (PLoS ONE, 2026)
Objectives This study aimed to determine reference intervals (RI) for thyroid hormones based on thyroid antibody levels using different autoanalyzer kits. Methods RI for Thyroid-stimulating hormone (TSH), free thyroxine (fT 4 ) and free triiodothyronine (fT 3 ) were determined according to thyroid antibody levels and independently of thyroid antibody levels using the R statistical program and RefineR algorithm. Results Significant differences in RIs were found between antibody-positive (Ab(+)) and antibody-negative (Ab(–)) individuals. TSH RI varied most notably in Abbott and Siemens analyzers. In females, Abbott showed higher TSH RIs in the Ab(+) group (0.41–7.44 mU/L) than in Ab(–) (0.24–3.50 mU/L). In males, Roche and Beckman exhibited the greatest differences (Roche Ab(+): 0.19–5.77; Ab(–): 0.44–3.63; Beckman Ab(+): 0.12–5.23; Ab(–): 0.39–3.96 mU/L). For fT4, Roche showed increased RIs in females with Ab(+) status (11.42–20.42 vs. 10.34–19.35 pmol/L). In males, Beckman and Siemens autoanalyzers also indicated notable differences. Conclusion Antibody status significantly affects thyroid hormone RI, particularly for TSH. These findings highlight the need for antibody-specific RI and further standardization in establishing reference intervals.